Document Generation untuk Chatbot Berbasis Aturan dengan Pendekatan Template Method - Ishlakhuddin, Fauzan; Santosa, Yaqutina Marjani; Nugraha, Nur Budi (Politeknik Harapan Bersama, 2022)
The world of education has an important role in the development of a country, innovations and initiatives that support educational activities are needed to support these activities. One of the innovations in the world of education is the convenience of students to access the results (development) of their lectures from anywhere. Chatbot has convenience in terms of service, because using a chatbot can make it easier to spread data. Provision of accurate and relevant data in real time is also needed so that the deployment will be faster and easier. Document generation is a method that can be used to create lecture-related files in real time, quickly and accurately. From the test results it was found that the files created were accurate and relevant to the SIAKAD system that had been used.The world of education has an important role in the development of a country, innovations and initiatives that support educational activities are needed to support these activities. One of the innovations in the world of education is the convenience of students to access the results (development) of their lectures from anywhere. Chatbot has convenience in terms of service, because using a chatbot can make it easier to spread data. Provision of accurate and relevant data in real time is also needed so that the deployment will be faster and easier. Document generation is a method that can be used to create lecture-related files in real time, quickly and accurately. From the test results it was found that the files created were accurate and relevant to the SIAKAD system that had been used.